Wladimir Eliasberg papers - Eliasberg, Wladimir, 1887-1969.
Correspondence, writings on Sigmund Freud and other topics, and obituaries. Includes letters from Eugen Bleuler, Kurt Lewin, Albert Moll, Paul Schilder, Ernst Simmel, Wilhelm Stekel, and Walther Theodor Winkler.
In part, photocopies.
Psychiatrist and author.
In German and English.
Forms part of: Sigmund Freud collection.
Keywords: Bleuler, Eugen, -- 1857-1939 -- Correspondence; Freud, Sigmund, -- 1856-1939.; Lewin, Kurt, -- 1890-1947 -- Correspondence; Moll, Albert, -- 1862- -- Correspondence; Schilder, Paul, -- 1886-1940 -- Correspondence; Simmel, Ernst, -- 1882-1947 -- Correspondence; Stekel, Wilhelm, -- 1868-1940 -- Correspondence; Winkler, Walther Theodor, -- 1914- -- Correspondence; Psychoanalysis; Authors; Psychiatrists